Dual Legitimacy and Constitutional Court’s Role in Presidential Impeachment Review - Ahmad Ahmad; Bagus Wirayuda; Brian Rahmat Ismail; Muhamad Fariq Haqi; Mohammad Nurkholis (Universitas Muhammadiyah Tangerang, 2025)
The role of the Indonesian Constitutional Court within Indonesia’s constitutional system is particularly significant in the impeachment mechanism of the president and/or vice president. Following the amendments to the 1945 Constitution, the Court is vested with authority under Article 24C, paragraph (2), to examine and decide upon opinions of the House of Representatives regarding alleged serious legal violations committed by the President. Nevertheless, tension arises between the political legitimacy of the DPR as a representative institution and the legal legitimacy of the Constitutional Court as a judicial body. This tension produces what may be described as dual legitimacy, namely the contestation between political authority and legal authority within the impeachment process. This study critically analyzes the position of the Constitutional Court in such proceedings and juridically examines the limits of its authority as determined by the Constitution. The findings indicate that although the Court plays a decisive role in assessing the legality of accusations, the final decision on removal remains with the People’s Consultative Assembly. This confirms that impeachment in Indonesia is a hybrid process combining legal and political elements, thus requiring clearer regulation and stronger institutional design to prevent overlapping authority among state institutions.